1995
DOI: 10.1159/000184585
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Thyroglobulin Levels in Monitoring the Treatment of Congenital Hypothyroidism

Abstract: We have previously reported on high thyroid-stimulating hormone (TSH) concentrations in clinically euthyroid children with congenital (CH) undergoing appropriate treatment. Whether this TSH is biologically active or not is still unclear. It has been shown that ectopic thyroid tissue does not involute during thyroxine (T4) therapy and thus can continue to secrete thyroglobulin (Tg). This study was undertaken to determine whether the Tg levels in ectopic CH infants represent residual thyroid tissue st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Indeed, along with a decrease in TSH levels following treatment with L-thyroxin, the Tg levels also returned to normal values. It was shown that Tg is TSH dependent and that its levels reflect TSH stimulation of the thyroid gland [15,16]. Our infant was not treated with iodine-containing antiseptic solutions, as these agents are not used in our department, nor were any iodine contrast media used on our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, along with a decrease in TSH levels following treatment with L-thyroxin, the Tg levels also returned to normal values. It was shown that Tg is TSH dependent and that its levels reflect TSH stimulation of the thyroid gland [15,16]. Our infant was not treated with iodine-containing antiseptic solutions, as these agents are not used in our department, nor were any iodine contrast media used on our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, along with a decrease in TSH levels following treatment with L‐thyroxin, the Tg levels also returned to normal values. It was shown that Tg is TSH dependent and that its levels reflect TSH stimulation of the thyroid gland 15, 16. Our infant was not treated with iodine‐containing antiseptic solutions, as these agents are not used in our department, nor were any iodine contrast media used on our patient.…”
Section: Discussionmentioning
confidence: 99%